Nurturing Factual Model of Cadets at the Politeknik Ilmu Pelayaran (PIP) Semarang - I Kadek Laju; Soesanto Soesanto; S Martono; Muhsin Muhsin (Universitas Negeri Semarang, 2021)
Nurturing that applied at Politeknik Ilmu Pelayaran (PIP) Semarang is currently still using a conventional model that is oriented to results or outcomes. This is shown in the nurturing process and the output targets listed in the Guidelines for the Nurturing Pattern for the BPSDM Transportation Cadets. The purpose of the study was to evaluate the weaknesses of the PIP Semarang cadet nurturing model. The evaluation was carried out to produce a nurturing method that was in accordance with the needs of the cadets at PIP Semarang. This research was conducted using a qualitative approach. The data used in the analysis is sourced from primary data obtained through interview techniques with data sources in the field and direct observations carried out by researchers. Meanwhile, secondary data was obtained through a study of existing documents, especially regarding various regulations in the PIP Semarang environment. Through the data analysis conducted, the evaluation results show that there are difficulties in adapting and learning difficulties experienced by cadets at PIP Semarang.